A Critical Narrative of Salafi–Wahhabi Discourse on Social Media - Muhammad Zainal Abidin; Ridhatullah Assya’bani (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2025)
This article aims to explore the discourse narrative evolving from Salafi-Wahhabi scholars regarding Kalam (Islamic theology), including how this discourse is generated and disseminated. What was once a concern confined to a limited circle has now become a public issue accessible to anyone from diverse backgrounds. Thus, the discourse battle within Islamic thought has shifted its battleground, considering vastly different circumstances compared to its development in the past. This research falls under media studies utilizing content analysis. It delves deeply into the issues circulating on social media related to Salafi-Wahhabi preaching about Kalam (Islamic Theology). The findings of this article are twofold: Firstly, Salafi-Wahhabi groups often emphasize a discourse rejecting the use of theological speculation and philosophy in religious understanding. They argue that the Quran and Hadith as primary Islamic sources suffice as guidance in religious practices. They tend to reject rational and philosophical approaches in comprehending Islamic teachings, prioritizing a literal textual understanding. Salafi-Wahhabis stress literalism in religious interpretation and frequently view the understanding of Kalam (rational theology) as potentially confusing to creed and introducing concepts not found in sacred texts. Secondly, Salafi-Wahhabi groups have effectively utilized social media to disseminate their religious narrative. They possess significant financial support for producing high-quality religious content. Technological advancements have allowed them to reach broader and deeper audiences with their narrative. Social media has become a crucial tool in reinforcing their religious understanding and perspectives while also posing challenges in terms of social media literacy and religious tolerance.